Safety and Efficacy of Microneedling Procedure in Treating Warts: Retrospective Analysis - Syeda, Sakina; Zafar, Alina; Ahmed, Saqlain; Akbar, Aiza Ali; Syeda, Wajiha Batool; Raja, Ayesha Ijaz (Indus Journal of Bioscience Research, 2024)
Introduction: Warts are one of the most prevalent viral disorders that affect epidermal keratinocytes and are cutaneous signs of human papilloma virus infection. Warts are usually slow-growing and self-limiting, but treatment is required because of the possibility of transmission, aesthetic effect of the warts, psychological impact, excruciating pain, and disfiguring effects. Methodology: This was a retrospective analysis of 130 patients with warts to determine the effectiveness and safety of the needling procedure and the factors that could affect the outcomes. Results: In total, 130 patients were included in this study. Females made the major section (70.8%) of the study population, and the mean age of the study sample was 24.14 ± 5.9 years. The number of lesions ranged from single to 75. Time for the warts being symptomatic to present to clinic was 1 to 15 weeks, and 16.9% patients had pain when they presented to clinic. The sole (33.8%) and toes (17.7%) of feet were the most common sites of warts. The duration for which the patient had been symptomatic and the symptom of pain at presentation were significant factors for healing (p < 0.05). Conclusion: Needling procedures are still effective method for treating warts; in our study, 64.62% participants out of 130 showed improvement at certain level. Person perception and patient satisfaction were subjective.